Factors Affecting on the Adoption of International Financial Reporting Standards: Iraqi Evidence - Sharif, Hazhar P. (2010)
The purpose of this study is to identify the factors that could explain the adoption of International Financial Reporting Standards (IFRS) by Iraqi companies. This study explains why Iraq, a developing country still has not adopted the IFRS, even though adoption of IFRS would result in improving the quality of corporate reporting practices and enhances the comparability, reliability, and relevancy of financial statements. This study also points out that there is an urgent need for Iraq to adopt the IFRS instead of still continues to practice the Unified Accounting System. More importantly, this study attempts to understand the factors that could encourage the adoption of IFRS by Iraq. The following factors have been selected: government policy, capital market, education level, professional bodies, and company size. Our results indicate that there are significant relationship between four variables which are (capital market, education level, professional bodies, company size) and adoption of IFRS except government policy. This study carried out using the quantitative method used questionnaires to collect primary data and, using data from 50 questionnaires that were distributed on Iraqi companies that are registered on the Iraqi stock exchange was analyzed using the package of SPSS.